Beads selection system using grid-based technique / Siti Nuramalina Johari - Johari, Siti Nuramalina (2012)
Beads designs were changing and have improvement from time to time. Beaded clothing transforms simple clothing into unique treasures by adding vivid and colorful beads and hand sculpted wires. Nowadays beaded clothing has been widely used for fulfilling fashion needs. At this time, making, choosing and determination of bead on garments was made by using the sketch or through imaginative. This makes it difficult for beads enthusiast to choose the type and color of appropriate beads on their clothing. This thesis is a new innovative research which will combine traditional way together with modern style to help designers choose the beads on their customer's clothes. It focuses on selecting the appropriate form of beads in single floral motif image. The objective of this thesis is to segment the floral motif via segmentation process by using histogram based segmentation and clustering method. From there, Image enhancement is then used to improve the floral image before detecting the boundary to retrieve the image. Then, this system will detect shape of a floral motif using boundary based technique. Next, Grid based method is used to insert the beads and the system is evaluated by checking the functionality of the system whether it works or not. The result shows that boundary based detection can be used to detect the shape of the floral motif image. Grid based technique can be used to insert the selected beads into the detected shape of the image.